Geological and Geochemical Characteristics of the Terrestrial Lower Jurassic Shale in Tarim Basin and its Favorable Exploration Areas - Wang, Qifeng; Tang, Haifa; Guo, Zhi; Cheng, Gang; Lv, Zhikai; Liu, Qunming (Frontiers in Earth Science, 2022)
Large amounts of conventional gas resources that originated from terrestrial Lower Jurassic shale were discovered in the Tarim Basin, indicating promising exploration prospects for shale gas resources, whereas limited understandings were obtained on the geological and geochemical characteristics of the Lower Jurassic shale. In this study, based on cores of exploration wells and field outcrops, total organic carbon (TOC) pyrolysis, microscopic composition, organic elements, vitrinite reflectance, x-ray diffraction, and methane isothermal adsorption experiments were carried out on Lower Jurassic shale in the Tarim Basin. The results show that the TOC content of shale is relatively high, but the TOC content of shale in different regions is quite different. Among them, the Kuqa Depression is the highest (more than 3%), the Southwest Tarim Basin is second (more than 1%), and the East Tarim Basin is the lowest. The main types of kerogen in shale are mainly type III and type II2. The thermal evolution maturity of shale in different regions is quite different; the highest Ro of shale in the Southwest Tarim Basin is more than 2.0% and that of shale in the Kuqa depression is higher than 1.5%, both of which have entered the stage of high-over-mature evolution, and the shale in the East Tarim Basin is only in the low maturity–mature stage. The overall content of brittle minerals such as quartz in shale is greater than 40%, which has good fracturing properties. The adsorbed gas content of shale is high, but there is a great difference (0.5–4 m3/t), which is related to the large difference in the abundance of organic matter, thermal maturity, and clay mineral content of shale. Therefore, the Lower Jurassic shale gas in the Tarim Basin has good prospects for exploration. Based on the superposition method of the main controlling geological factors, it is predicted that the favorable areas for shale gas exploration are mainly located in the Keshen and Yinan-Yeyun areas of the Kuqa Depression and the Caohu Sag-Mandong area of the East Tarim Basin. This research not only provides basic data for the evaluation of shale gas resources in our country, but also provides certain guidance for the exploration of Lower Jurassic shale gas in the Tarim Basin.